Attentional bias and treatment adherence in substitute-prescribed opiate users. (July 2015) - Charles, M.; Wellington, C.E.; Mokrysz, C.; Freeman, T.P.; O'Ryan, D.; Curran, H.V.
Abstract: Background: Attentional bias (AB) is implicated in the development and maintenance of substance dependence and in treatment outcome. We assessed the effects of attentional bias modification (ABM), and the relationship between AB and treatment adherence in opiate dependent patients. Method: An independent groups design was used to compare 23 opiate dependent patients with 21 healthy controls. Participants completed an AB task before either a control or an ABM task designed to train attention away from substance-related stimuli. Pre- and post-ABM AB and craving were assessed to determine any changes. Relationships between treatment adherence ('using on top' of prescribed opiates or not) and AB, craving and psychopathology were also examined. Results: There was no baseline difference in AB between patients and controls, and no significant effect of ABM on AB or substance craving. However, treatment adherent patients who did not use illicit opiates on top of their prescribed opiates had statistically significantly greater AB away from substance-related stimuli than both participants using on top and controls, and reported significantly lower levels of craving than non-treatment adherent patients. Conclusion: Whilst we did not find any significant effects of ABM on AB or craving, patients who were treatment adherent differed from both those who were not and from controls in their attentional functioning and substance craving. These findings are the first to suggest that AB may be a within-treatment factor predictive of adherence to pharmacological treatment and potentially of recovery in opiate users. Highlights: We tested attentional bias modification in treatment-seeking opiate users. We also compared those who did and did not adhere to opiate substitution treatment. Attentional bias modification did not influence attentional bias or craving. Adherent patients had attentional bias away from opiate-stimuli and lower craving. Attentional bias may predict adherence in treatment-seeking drug users.